A new system for direct measurement of yarn mass with 1 mm. accuracy - Pinto, J. G. (2002)
In Textile production, measurement of the yarn mass in 1mm range is utmost importance to properly evaluate the evenness, as several irregularities occur in 1 to 4mm yarn length. Until present, measurements in 1mm range are still not directly performed. In this paper we present a direct mass measurement in 1mm range based on capacitive sensors and signal processing techniques. The results point out that the evaluation of yarn mass, with this approach, is feasible in the 1mm range. The new approach allows on-line measurement (1mm yarn mass) in a spinning frame for real-time control. Several Digital Signal Processing techniques are used to improve the results. A value of capacity variation is close to 2,08E-17 F for a 57 tex (0,057 g/m) yarn. It is possible, with this equipment, to detect small variations but signal to noise ratio (SNR) is still low. With the current electronic conditioning it is possible to detect these variation in spite it is in microvolt range. As a spin-off the developed sensor is being used in knitting machines to control the yarn break and bobbin end.